The PERSON restriction on periphrastic irrealis complementizers and the interpretation of subject pro - Ceong, Hailey Hyekyeong (Canadian journal of linguistics, 2019)
This squib demonstrates that in Korean, depending on the selectional relations between tense and complementizers, and the restriction on the subject under certain complementizers, first- and second-person subjects can be dropped without being construed with a discourse topic. Therefore, the contents of pro are not always recovered in the same way in discourse-oriented null subject languages (Huang 1984, Holmberg et al. 2009, Barbosa 2011).